Synthesis and characterization of bioactive zirconia toughened alumina doped with HAp and fluoride compounds - Singh V.K.; Reddy B.R. (My University, 2025)
Alumina-zirconia nanostructured composites (ZrO 2 addition by 20 wt%) were prepared using combined gelation-precipitation process. A modified sol-gel process has been developed to prepare nano structured spinel [MgAl 2O 4], Al 2O 3, ZrO 2 and their composite materials. This process is useful in retaining tetragonal phase of zirconia at room temperature, which provides transformation toughening in the nano composites. Dried gels powders were calcined up to 1250 °C. Similarly, hydroxyapatite powders were produced by wet-chemical method and calcined at different temperatures. All the dried gel and calcined powders were characterized by using X-ray diffraction, DTA/TGA and SEM. Samples were prepared by uniaxial pressing the composites powders using ZTA, HAp, MgF 2 and CaF 2 in different ratio. Incorporation of CaF 2 and MgF 2 as a source for fluorine was also done to improve the sinterability of composites. The samples were sintered at 1400 °C for three hours. Densification and mechanical behaviour of sintered samples were observed. Bioactivities of all compositions were tested using SBF solution and then characterizing by FTIR. The main objective of work was to dope ZTA nano composites with HAp and fluoride compounds to obtain better sinterability at lower temperatures. Then evaluate the obtained ZTA based bioactive composite ceramics that have high mechanical strengths. This study verifies the bioactivities of HAp-added ZTA composites. © 2012 Elsevier Ltd and Techna Group S.r.l. All rights reserved.